2020
DOI: 10.1002/micr.30554
|View full text |Cite
|
Sign up to set email alerts
|

Survival rates and risk factors for failure using an interposition vein graft for fingertip amputations with segmental vessel defects

Abstract: PurposeThis study aimed to compare survival rates and risk factors of replantation failures using an interposition vein graft in fingertip amputations with segmental vessel defects with those using simple end‐to‐end anastomosis in amputations.Patients and methodsBetween 2004 and 2015, 776 (647 males and 129 females) with single Zone I or II amputations of digits underwent replantation. Among these, simple end‐to‐end anastomosis was performed in 698 replantations, while interposition vein grafts were used for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Moreover, even if the intima is intact, damage to the soft tissue may affect the circulation in cases of avulsed or crushed amputation. [13][14][15][16] Lee et al reported that there was no difference in the success rate between the groups with and without vein grafts. 6 However, they also reported that vein graft should not be advocated, if the possibility of a meaningful functional recovery of the digit is low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, even if the intima is intact, damage to the soft tissue may affect the circulation in cases of avulsed or crushed amputation. [13][14][15][16] Lee et al reported that there was no difference in the success rate between the groups with and without vein grafts. 6 However, they also reported that vein graft should not be advocated, if the possibility of a meaningful functional recovery of the digit is low.…”
Section: Discussionmentioning
confidence: 99%
“…Vein grafting with two anastomoses doubles the possibility of technical failure and thrombogenic response to vessel trauma, possibly promoting flow disturbances and subsequent thrombus formation. [13][14][15][16] It is imperative that an adequate resection of injured vessels is performed, which may require an interpositional graft to bridge the gap. Recent studies have suggested that the success rate is similar between replantation/revascularization with and without vein graft.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, we used an interposition vein graft harvested from the distal volar forearm. 4 Veins and nerves were repaired if suture was possible; however, if it was difficult, nerve repair was not performed, and venous drainage was provided by an external bleeding method with a fish-mouth incision at the distal end of amputations for approximately 7 days. 5 The nail bed and distal fragment was harvested from the distal stump and grafted, and a palmar advancement flap was performed.…”
Section: Replantationmentioning
confidence: 99%
“…Although the success rate of interposition vein grafting for fingertip replantations is acceptable at 80.8 percent, it is lower than the survival rate of 93.1 percent in the simple end-to-end anastomosis group. 26 Another method of repairing vessel gaps during replantation is transposition vein grafting. In a single-institution study on thumb replantation, the authors report transposing the vein on the dorsal radial side of the index finger so that only one anastomosis is performed.…”
Section: Upper Extremitymentioning
confidence: 99%